The application of predicted habitat models to investigate the spatial ecology of demersal fish assemblages - Moore, Cordelia; Harvey, Euan; Van Niel, K. (Springer-Verlag, 2010)
Benthic habitats are known to influence the abundance and richness of demersal fish assemblages; however, little is known about how habitat structure and composition influences these distributions at very fine scales. We examined how the benthic environment structures marine fish assemblages using high-resolution bathymetry and accurate predicted benthic habitat maps. Areas characterised by a mosaic of habitat patches supported the highest richness of demersal fishes. A total of 37.4% of the variation in the distribution of the fish assemblage was attributed to 6 significant variables. Depth explained 23.0% of the variation, with the boulders explaining 12.6% and relief 1.4%. The remaining measures (seawhips, light/exposure and solid reef) provided a small (<1.0%) but significant contribution. Identifying components of the benthic environment important in structuring fish assemblages and understanding how they influence the spatial distribution of marine fishes is imperative for better management of demersal fish populations